Spontaneous spinal hemorrhage as the complication of low-molecular-weight heparin: A case report (Indian Journal of Case Reports, 2024)
A 57-year-old woman with good past health presented with sudden-onset paraplegia after receiving aspirin, clopidogrel, and low-molecular-weight heparin (LMWH) for suspected acute coronary syndrome. She suffered from spontaneous spinal hemorrhage which was intradural in location. She remained paraplegic despite clot evacuation and 2 months of rehabilitation. Caution on uncommon sites of bleeding should be taken when prescribing anti-thrombotic drugs. Of note, spontaneous spinal hemorrhage is one of the black box warnings of LMWH.